Real-world outcomes of Finerenone in patients with diabetic kidney disease in Saudi Arabia - Mohamed A. Albekery; Ibrahim S. Alhomoud; Khalid A. Alamer; Ahmed A. Alanazi; Abdulmohsen E. Al Mulhem; Ahmed E. Alnaim; Fahad M. Almulhim; Abdulrahman S. Almulhim; Saleh A. Al Makhaytah; Reema H. Aldawsari; Muthana Al Sahlawi; Mohammed Y. Almulhim (PLoS ONE, 2026)
Background Diabetic kidney disease (DKD) represents a significant microvascular complication associated with type 2 diabetes mellitus (T2DM), markedly elevating the risk of kidney failure, cardiovascular events, and premature mortality. Despite advancements in therapeutic management, such as renin–angiotensin–aldosterone system (RAAS) blockade and sodium–glucose cotransporter 2 (SGLT2) inhibitors, residual risk remains significant. Finerenone, a novel nonsteroidal and selective mineralocorticoid receptor antagonist (MRA), has demonstrated substantial cardiorenal benefits in clinical trials; however, real-world data, especially from Saudi Arabia, remain limited. Method This single-center, retrospective cohort study. All adult patients (≥18 years) who received finerenone as part of routine clinical care were eligible if they met either of the following criteria: (1) documented diabetic kidney disease (DKD) based on KDIGO-aligned clinical criteria, including diabetes mellitus with chronic kidney disease manifested by albuminuria/proteinuria and/or reduced eGFR; (2) and/or a urine protein-to-creatinine ratio (uPCR) >0.3 mg/mg. Longitudinal changes in uPCR, eGFR, and serum potassium were analyzed using linear mixed-effects models adjusted for relevant clinical covariates. Results A total of 75 patients prescribed finerenone were screened, of whom 67 met the inclusion criteria. The median age was 63 years, and 53.7% were female. Comorbidities were highly prevalent, including diabetes mellitus (89.6%), hypertension (97.0%), dyslipidemia (92.5%), heart failure (56.8%), and coronary artery disease (40.3%). A significant effect of time on uPCR was observed (F[3,193] = 3.457; P = 0.018), with a mean reduction of 0.464 mg/mg after six months (95% CI, −0.895 to −0.034; P = 0.027). The estimated eGFR slope after finerenone initiation was −1.08 mL/min/1.73 m² per month (95% CI −1.74 to −0.41; P = 0.002), corresponding to an annualized decline of approximately −12.9 mL/min/1.73 m² per year. Serum potassium increased modestly at early follow-up points (F[5,245] = 4.008; P = 0.002), rising by +0.209, + 0.256, and +0.286 mmol/L at the first three readings (P = 0.029, 0.005, and 0.006, respectively), then plateaued thereafter (P > 0.5). Conclusion Finerenone use among DKD patients in Saudi Arabia was associated with significant reductions in proteinuria, an early decline in eGFR that requires cautious interpretation, and an overall favorable safety profile. These real-world findings align with results from pivotal clinical trials and support the incorporation of finerenone into standard DKD management. Future multicenter prospective studies are warranted to confirm these outcomes and evaluate long-term cardiorenal benefits.